2014
DOI: 10.3109/02770903.2014.956893
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with disease severity in children with bronchiolitis

Abstract: During acute bronchiolitis infections, younger children and those with a history of prematurity were more likely to be admitted to the ICU with severe disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 24 publications
4
24
2
Order By: Relevance
“…During acute bronchiolitis infections, younger children and those with a history of prematurity were more likely to suffer from severe disease. 12 In the present study, we did not observe such correlation, since there were only 8.6% were preterm babies and 99% of children admitted with bronchiolitis in our hospital were ≤12 months of age. We observed that breastfeeding did do not have too significant impact on the severity of disease since 50/105 (47.6%) did not receive breastfeed.…”
Section: Discussioncontrasting
confidence: 39%
“…During acute bronchiolitis infections, younger children and those with a history of prematurity were more likely to suffer from severe disease. 12 In the present study, we did not observe such correlation, since there were only 8.6% were preterm babies and 99% of children admitted with bronchiolitis in our hospital were ≤12 months of age. We observed that breastfeeding did do not have too significant impact on the severity of disease since 50/105 (47.6%) did not receive breastfeed.…”
Section: Discussioncontrasting
confidence: 39%
“…In contrast to other studies, while admission to the ICU was associated with a history of premature birth (odds ratio [OR]: 1.7; 95% CI: 1.1–2.4, P  = 0.01), Sala et al [77] found no significant difference in the ICU LOS (106 [42–252] days vs. 106 [59–219] days; P  = 0.94) or in mechanical ventilation (OR: 1.1; 95% CI: 0.6–2.1; P  = 0.8) between infants with and without a history of prematurity. Similarly, Gijtenbeek et al [43] found no relation between gestational age and disease severity or in hospitalization LOS or use of mechanical ventilation and oxygen.…”
Section: Resultsmentioning
confidence: 82%
“…The number of patients assessed eligibility was decreased because we excluded infants aged younger than 2 months (13 infants), with low birth weight (7 infants), and those born before [26][27] . Therefore, including such infants is considered to be harmful for the homogeneity of study patients.…”
Section: Discussionmentioning
confidence: 99%